Thyroid metastases from a breast cancer diagnosed by fine-needle aspiration biopsy. Case report and overview of the literature - Lacka, K.; Breborowicz, D.; Uliasz, A.; Teresiak, M. (Experimental Oncology, 2012)
Aim: Intrathyroid metastases are uncommon in cytology practice. We report a case of metastatic lesion in the thyroid from breast carcinoma which was recognized in a fine-needle aspiration (FNA) biopsy and confirmed by immunohistopathology. In addition, we provide an overview of the literature describing similar cases. Study design: The patient was a 54-year old woman with a large, multinodular goiter and bilaterally enlarged lymph nodes in the supraclavicular areas. Fourteen years earlier she had undergone radical mastectomy followed by chemio- and radiotherapy due to a breast carcinoma. Results: FNA of the thyroid nodules showed a metastatic breast carcinoma and was followed by total strumectomy and lymphadenectomy. Histological reassessment of the surgical thyroid specimens as well as the neck lymph nodes revealed multiple breast metastases. This was strongly confirmed by immunohistochemical examinations, which revealed a positive staining for: CKMNF 116, CK7, CEA as well as for ER, PgR and HER2, and a negative staining for: CK20, thyroglobulin, TTF1, calcitonin, and chromogranin. Conclusion: Every new aggregate in the thyroid in patients with even a long-term history of cancer should be considered as potentially metastatic until proved otherwise. FNA could be helpful in the diagnosis of thyroid metastatic lesion, but it should be confirmed by immunohistopathology.